2019
DOI: 10.31258/jes.3.2.p.227-236
|View full text |Cite
|
Sign up to set email alerts
|

Interest and Factors Affecting Student in Choosing Social Departments

Abstract: The low interest of students choosing social studies majors (IPS) at the National High School is thought to be a problem that originates from within students and outside the student's self. The purpose of this study was to determine the factors that influence students' interest in choosing a social studies major at SMA 2 Tambang, in Kampar Regency, Riau Province. The population in this study were all students of class XI IPS, amounting to 170 people. The sample was determined using propotional random sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…A person's ideals will influence a person to have behavior with the aim of being able to achieve these goals (Yarnefi, et al, 2019). The results of this study are also in line with research (Nurtanto et al, 2017;Suyitno, 2016).…”
Section: The Influence Of Ambition On Interests In Choosing a Departmentsupporting
confidence: 88%
“…A person's ideals will influence a person to have behavior with the aim of being able to achieve these goals (Yarnefi, et al, 2019). The results of this study are also in line with research (Nurtanto et al, 2017;Suyitno, 2016).…”
Section: The Influence Of Ambition On Interests In Choosing a Departmentsupporting
confidence: 88%
“…Teachers in school with parents are a factor that influences students. Guidance and counseling provided by the teacher can direct student development (Liando, 2015;Yarnefi et al, 2019).…”
Section: Effect Of Teacher's Work Enthusiasm On Affective Learning Oumentioning
confidence: 99%
“…The socio-economic conditions of the students' families in Kampar District are related to the level of education of their parents, parents' jobs, parents' income, ownership of assets and social position in the community. Based on research conducted by Yarnefi et al, (2019), it was found that the family environment was able to influence student learning motivation.…”
Section: The Influence Of Learning Motivation On Students' Cognitive Ability Moderated By Family Socio-economic Conditionsmentioning
confidence: 99%